Perilaku Komunikasi Manusia Silver di Kota Medan - Rahmayani, Cindy; Sikumbang, Ahmad Tamrin (eScience Humanity Journal, 2024)
Humans are considered social creatures and cannot meet their daily needs alone This research discusses the communication behaviour of the silver community in the city of Medan The main questions of this study are: (1) What kind of communication behaviour does the Silver Man use? (2) What are the factors that affect the communication behaviour of the Silver Man in the city of Medan? The purpose of this study is to describe the communication behaviour of the Silver Man in the city of Medan This research is part of the field research category related to events in the field Using a mass-based qualitative descriptive approach to produce descriptive data in the form of text and oral words from people observed by the researcher